The Human retroviruses - Gallo, Robert C.; Jay, Gilbert (Academic Press, 1991)
This book presents twenty-four tightly focused reviews on the biology, molecular biology, pathology, and epidemiology of the human retroviruses, particularly HIV and HTLV (Types I and II), as well as animal model systems (simian retroviruses, STLV and SIV, and mouse models). Editor Robert C. Gallo is recognized as a co-discoverer of the AIDS virus.